Analisiss Kasus Marahi Suami Pulang Mabuk Seorang Isri Di Penjarakan Yang Ditinjau Persfektif Sosiologi Hukum - tresna, Muhammad arexsa budi (Peneliti.net, 2024)
This paper aims to find out and analyze the handling of cases of Domestic Violence (KDRT) Angry Husband Comes Home Drunk A Wife In Prison From a Legal Sociology Perspective? What are the factors that cause cases of Domestic Violence that occur to be subject to one year imprisonment? And How Sociological Analysis of Community Empowerment and Women's Empowerment The data analysis method used in this paper is a descriptive method is a research method used to describe problems that occur in the present or ongoing, aiming to describe what is happening as it should at the time of research is done. The results of research conducted on domestic violence obtained and described in this paper are related to the existence of external factors, including those caused by inequality in family relations which are also exacerbated by other factors such as religious environmental factors and permissive culture, while internal factors are usually caused by weak emotional management of perpetrators of violence when solving problems in the family. As for the protection and assistance that has been given to every victim of domestic violence, especially women and children